Endovascular Management of Cerebral Aneurysms of the Posterior Cerebral Artery - Li, Xin-Yu; Li, Cong-Hui; Wang, Ji-Wei; Liu, Jian-Feng; Li, Hui; Gao, Bu-Lang (Frontiers in Neurology, 2021)
Purpose To investigate the safety and efficacy of endovascular embolization of cerebral aneurysms at the P1-P3 segments of the posterior cerebral artery (PCA). Materials and methods Seventy-seven patients with 77 PCA aneurysms who were treated with endovascular embolization were enrolled, including 35 (45.5%) patients with ruptured aneurysms and 42 (54.5%) with non-unruptured ones. The pretreatment clinical data and aneurysm occlusion status after treatment and at follow-up were analyzed. Results All patients were successfully treated endovascularly, including coiling alone in 10 (13.0%) patients, stent-assisted coiling in 18 (23.4%), parent artery occlusion in the 25 (32.5%), and Pipeline embolization device (PED) in 24 (31.2%). Complete occlusion was achieved in 48 (62.3%) aneurysms, nearly complete occlusionresidual neck was in four (5.2%), and non-residual aneurysmcomplete occlusion in the other 25 (32.5%) at the end of embolization. Periprocedural complications occurred in eight patients, including acute thrombosis in seven (9.1%) and intraprocedural subarachnoid hemorrhage in one (1.3%), with the total complication rate of 10.4%. Follow-up was performed in 60 patients (77.9%) for 42±11 months, the mRS score was 0-2 in 55 (91.7%) patients, 3 in four patients (6.7%), and 6 in one patient (1.7%). Fifty-three (88.3%) patients (53 aneurysms) had stable or complete occlusion, and seven (11.7%) patients had aneurysm recurrence or non-complete occlusionresidual aneurysm. Among 19 patients treated with PED at follow-up, 15 aneurysms (78.9%) proceeded to complete occlusion while four (21.1%) aneurysms showed residual aneurysm cavity residual. Conclusion Endovascular embolization remains a good choice of treatment with high safety and efficacy for posterior cerebral artery aneurysms with abundant collateral circulation.